Advancement in Nanotheranostics for Effective Skin Cancer Therapy: State of the Art - Akhter, Md. H.; Ahsan, Mohamed Jawed; Rahman, Mahfoozur; Anwar, Siraj; Rizwanullah, Md. (Current Nanomedicine, 2020)
The skin cancer has become a leading concern worldwide as a result of high mortality rate. The treatment modality involves radiation therapy, chemotherapy or surgery. More often combination therapy of chemotherapeutic agents gives better solution over single chemotherapeutic agent. The Globocon report suggested that high incidence and mortality rate in skin cancer is growing day-to-day. This type of cancer is more prevalent in that area where a person is highly exposed to sunlight. The nanotechnology-based therapy is nowadays drawing attention and becoming a more important issue to be discussed. The nanotherapy of skin cancer is dealt with various approaches and strategies. The strategic based approaches imply nanoparticles targeting carcinoma cells, functionalized nanoparticles for specific targeting to cancer cells, receptor-mediated active targeting as nanoshells, nanostrutured lipid carriers, liposome, ethosome, bilosome, polymeric nanoparticle, nanosphere, dendrimers, carbon nanotubes, quantum dots, solid lipid nanoparticles and fullerenes which are highly efficient in specific killing of cancer cells. The passive targeting of chemotherapeutic agents is also helpful in dealing with carcinoma due to enhanced permeability and retention effect (EPR). The article outlines nano-based therapy currently focused globally, and the outcomes of the therapy as well.
Keywords: carcinoma cells